Chronic Obstructive Pulmonary Disease in Latin America - Rogelio Perez-Padilla; Ana Maria B. Menezes (Ubiquity Press, 2019)
The PLATINO and PREPOCOL population-based studies documented the prevalence of chronic obstructive pulmonary disease (COPD) in several Latin American (Mexico City, Sao Paulo, Montevideo, Santiago and Caracas) and Colombian (Medellin, Bogota, Barranquilla, Bucaramanga and Cali) cities. COPD ranged between 6.2 and 19.6% in individuals ≥40 years of age, with substantial rates of underdiagnosis (up to 89%) but also overdiagnosis, mostly due to the lack of spirometric confirmation. The main risk factor was tobacco smoking, but male gender and age were also associated with COPD. COPD in never smokers represented about one third of the cases and was associated with previous history of tuberculosis or a diagnosis of asthma. COPD associated with biomass smoke exposure was a common clinical phenotype in Latin America, found as a risk factor in PREPOCOL and other observational studies in the region. Smoking has been decreasing in Latin America and efforts have been made to implement cleaner biomass stoves. Unfortunately, treatment of COPD in Latin America remains highly variable with low rates of smoking cessation counselling, low use of inhaled bronchodilators and influenza vaccination. A primary-care approach to COPD, particularly in the form of integrated programs is lacking but would be critical to improving rates of diagnosis and treatment of COPD.